ANALISIS KOMPARATIF PROSES PIROLISIS DARI BAHAN SAMPAH PLASTIK DAN BIOMASSA TERHADAP HASIL PRODUK - Ridhuan, Kemas; wahyudi, Tri cahyo; Antonio, Diego; Renaldi, Riki (TURBO [Tulisan Riset Berbasis Online], 2025)
Pyrolysis is a process of heating materials at high temperatures with little or no oxygen to chemically break down materials, to produce products such as fuel and liquid smoke. The purpose of this study was to determine the process, quantity, and characteristics of the products obtained from plastik waste and biomass. This research method uses a barner fueled by LPG gas. Using raw materials of LDPE plastik waste and biomass (rice husk) with a weight of 1.5 kg each. Using a batch type pyrolysis reactor and a straight pipe condenser with a diameter of 1 inch and a length of 4 m. The results showed that the two raw materials produced significantly different product proportions. LDPE pyrolysis produced a liquid product with a volume of 419 (mL) and a solid of 0.825 (kg), and had a higher calorific value of 10648.21 (kJ/kg) than rice husk. Meanwhile, rice husk pyrolysis produced a larger liquid (742 mL) with 0.316 kg of lower solids and a lower calorific value (8761.33 kJ/kg). This difference confirms that the type of feedstock significantly determines the quality and quantity of bio-oil or pyrolysis oil produced, which is crucial for renewable energy development and waste management.